2015
DOI: 10.12973/eu-jer.4.3.124
|View full text |Cite
|
Sign up to set email alerts
|

Learning Mathematics in English at Basic Schools in Ghana: A Benefit or Hindrance?

Abstract: Facilitating effective mathematics learning and higher mathematics achievement have long been recognized as a key to the scientific and technological advancement of the African continent. While the central role that language proficiency plays in mathematics teaching and learning has received an overwhelming research attention in the literature over the past two decades, this is not the case among African policy-makers and political leaders. Drawing mainly from our professional experiences as mathematics educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Moreover, MP is broken down into 5 strands: Conceptual understanding, procedural fluency, strategic competence, adaptive reasoning, and productive dispositi on (Cordova & Tan, 2018). Fredua-Kwarteng & Ahia (2015), explained the each strand as follows: conceptual understanding 'is about comprehension of mathematics concepts, operations, and their relationships'; procedural fluency 'refers to the knowledge and skills to apply mathematical procedures flexibly and appropriately in accordance with the contexts'; strategic competence 'is the ability to formulate, represent and solve mathematical problems'; Adaptive reasoning 'relates to the capacity to explain things using logic, thought reflection, and justification'; and productive disposition 'involves the development of positive attitude toward mathematics ' (Pein et al, 2015;Buxton et al, 2013).…”
Section: Athematics Proficiencymentioning
confidence: 99%
“…Moreover, MP is broken down into 5 strands: Conceptual understanding, procedural fluency, strategic competence, adaptive reasoning, and productive dispositi on (Cordova & Tan, 2018). Fredua-Kwarteng & Ahia (2015), explained the each strand as follows: conceptual understanding 'is about comprehension of mathematics concepts, operations, and their relationships'; procedural fluency 'refers to the knowledge and skills to apply mathematical procedures flexibly and appropriately in accordance with the contexts'; strategic competence 'is the ability to formulate, represent and solve mathematical problems'; Adaptive reasoning 'relates to the capacity to explain things using logic, thought reflection, and justification'; and productive disposition 'involves the development of positive attitude toward mathematics ' (Pein et al, 2015;Buxton et al, 2013).…”
Section: Athematics Proficiencymentioning
confidence: 99%
“…Researchers have consistently shown that attitudes toward mathematics play a crucial role in students' engagement and achievement in the subject [5,10,14,16]. Mathematics anxiety, in particular, has been identified as a significant barrier to learning, with girls often experiencing higher levels of anxiety compared to boys [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in Africa, major stakeholders-the government, parents, and educated elites-tend to exhibit significantly negative attitudes towards speaking the indigenous languages within school compounds [15,21,22]. Oftentimes, speaking the indigenous languages is considered a disgraceful act, and students are sometimes punished accordingly.…”
Section: Introductionmentioning
confidence: 99%